Comparative study of plain CT head versus MRI brain for detecting acute posterior fossa infarct - Acharya , Sandeep; Poudel, Saurav; Parajuli , Bivusha; Kaphle, Pratibha (Medical Journal of Eastern Nepal, 2025)
Background: Posterior fossa infarcts present diagnostic challenges due to their deep location and subtle clinical presentation. Although non-contrast computed tomography (NCCT) is widely utilized due to its accessibility and rapid imaging capabilities, its sensitivity in detecting these infarcts is lower than diffusion-weighted magnetic resonance imaging (DW MRI), which remains the gold standard. Methods: A prospective analytical study was conducted over the period of 15 months at a tertiary care centre in Nepal. A total of 150 patients with a clinical suspicion of posterior fossa stroke underwent NCCT, followed by DW MRI within 24 hours of symptom onset. The NCCT findings were compared with DW MRI’s to assess the sensitivity, specificity, positive predictive value, and negative predictive value in detecting acute infarcts. Results: Of the 150 patients, 93 (62%) were confirmed to have an acute posterior fossa infarct on DW MRI. The anatomical distribution included infarcts in the midbrain (8.67%), pons (20.00%), cerebellum (28.00%), and medulla (5.33%). NCCT demonstrated a sensitivity of 77.42% and a specificity of 64.91%, with a positive predictive value of 78.26% and a negative predictive value of 63.79%. Clinical features such as headache, high blood pressure, dizziness, loss of consciousness, and hemiparesis were significantly more common in MRI-positive cases. Conclusion: Although NCCT is an essential initial imaging tool in resource-limited settings, its moderate sensitivity and specificity underscore its limitations in detecting posterior fossa infarcts. DW MRI remains superior, particularly in patients with high-risk clinical features, emphasizing the need for integrated clinical-imaging protocols to optimize stroke diagnosis and management.